Environmental Impact Assessment (EIA) of a gold mine tailing through the multi-criteria decision making tool - AK Darban; RD Webster; HH Yarhosseini; B Malekmohammadi; AR Yavari; Arabyarmohammadi (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
Gold mine tailings dams are a high risk part of mining as they contain hazardous materials such as cyanide, mercury and arsenic from processing operations which present a risk to the public and to the environment. When tailing dams fail, the impact is disastrous for humans and the natural environment. The International Commission on Large Dams (ICOLD) collected 221 case records of tailing facility failure incidents worldwide to determine the causes of these incidents. The main causes of these incidents and reported cases of failure were found to be lack of control during the construction, lack of control of the water balance and a general lack of understanding of the features that control safe operations. The important elements to improve the safety and stability of tailings disposal facilities are geotechnical investigation, engineered design, construction, operation and monitoring of the tailings storage facility. Quality engineering is essential in the construction of a fill dam because the materials used have lower strength properties than the concrete dams thus the performance and safety of tailing dam is very important. In this research, the application of Multi Criteria Decision Making (MCDM) methods has been investigated in the Environmental Impact Assessment (EIA) process. For this purpose, Zarshoran Gold mine in the north west of Iran has been selected as a case study. The ability of MCDM methods in EIA has been tested in two parts. In the first part, the best site for dumping tailingss in the case study area has been identified by using TOPSIS method. The weights and criteria are specified to rank the sites and one of the sites has been chosen as the best place in the study area. Results show that the TOPSIS is a powerful method in the EIA process for identifying significance environmental impact and sorting the alternatives.